2019
DOI: 10.4143/crt.2018.460
|View full text |Cite
|
Sign up to set email alerts
|

KIF11 Functions as an Oncogene and Is Associated with Poor Outcomes from Breast Cancer

Abstract: Purpose The study aimed to search and identify genes that were differentially expressed in breast cancer, and their roles in cancer growth and progression. Materials and Methods The Gene Expression Omnibus (Oncomine) and The Cancer Genome Atlas databases ( https://cancergenome.nih.gov/ ) were screened for genes that were expressed differentially in breast cancer and were closely related to a poor prognosis. Gene expressions were verified by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 37 publications
4
53
0
Order By: Relevance
“…Similar study was also performed and reported by Song et al, showing the relationship between high expression of KIF15, KIF20A, KIF23, KIF2C, KIF4A and poor prognosis [27]. Moreover, KIF11 was identified as an oncogene in breast cancer through prompting cell proliferation, colony formation, cell migration while inhibiting cell apoptosis [28]. Li et al reported that KIF23 is able to promote the development of gastric cancer through stimulating the expression of Ki-67 and PCNA, thus accelerating cell proliferation [29].…”
Section: Agingsupporting
confidence: 84%
“…Similar study was also performed and reported by Song et al, showing the relationship between high expression of KIF15, KIF20A, KIF23, KIF2C, KIF4A and poor prognosis [27]. Moreover, KIF11 was identified as an oncogene in breast cancer through prompting cell proliferation, colony formation, cell migration while inhibiting cell apoptosis [28]. Li et al reported that KIF23 is able to promote the development of gastric cancer through stimulating the expression of Ki-67 and PCNA, thus accelerating cell proliferation [29].…”
Section: Agingsupporting
confidence: 84%
“…CEP55 acts as a tumor promoter in cancers of the lung, breast and pancreas, and it has been reported to be associated with metastasis in renal cell carcinoma . Kinesin family member 11 (KIF11) acts as an oncogene in meningioma and is also associated with poor outcomes in meningioma, breast and oral cancer . In our study, using the LASSO Cox regression model, we succeeded in integrating multiple genomic and protein markers into one model with high prognostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al found high expression of KIF11 predicted a unfavorable prognosis in clear cell renal cell carcinoma [ 25 ]. Zhou et al also found KIF11 functioned as an oncogene and was associated with poor outcomes in breast cancer patients [ 26 ]. Chen et al found KIF11 overexpression was significantly associated with shorter relapse-free survival times in HCC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%